Review of Patrick Burke. 2008. Come In And Hear The Truth: Jazz and Race on 52nd Street. Chicago and London: University of Chicago Press. - Coleman, Kwami (Current Musicology, 2010)
In today's Manhattan, the street signs on Fifty-second Street between Fifth and Seventh Avenues tell passersby that they are on "Swing Street;' even though nothing about the towering skyscrapers and the moving mass of people in business suits reflect this locale. Instead, what the street signs point to is a Fifty-second Street of the past: a collection of nightclubs and other establishments that jazz critics and scholars have designated as the birthplace of bebop, one of jazz's paradigm-shifting genres.